Molecular insight for the role of key residues of calreticulin in its binding activities: A computational study. (April 2020) - Yang, Hongyi; Ahmad, Zainab Ameir; Song, Yuhua
Graphical abstract: Highlights: Calreticulin (CRT) C105A, C137A and W319A mutations changed local backbone flexibility and secondary structure. C137A mutation decreased overall size of CRT and formed new inter-domain contacts. C105A, C137A and W319A mutations changed dynamical correlated motions between residues of CRT. Abstract: Calreticulin (CRT) is localized to and has functions in multiple cellular compartments, including the cell surface, the endoplasmic reticulum, and the extracellular matrix. Mutagenesis studies have identified several residues on a concave β-sheet surface of CRT critical for CRT binding to carbohydrate and other proteins/peptides. How the mutations of these key residues in CRT affect the conformation and dynamics of CRT, further influencing CRT binding to carbohydrates and other proteins to signal the important biological activities remain unknown. In this study, we investigated the effect of three key point mutations (C105A, C137A and W319A) on CRT conformation and dynamics via atomistic molecular dynamics simulations. Results show that these three key residues mutations induced the changes of CRT local backbone flexibility and secondary structure of CRT N-domain, which could further affect CRT's binding activity. C137A mutation led to dramatic decrease of the overall size of CRT due to the P-domain fold back to the globular domain and formed new inter-domain contacts, which can cause blockage of CRT's binding with other large substrates. Furthermore, for CRT concave β-strand surface patch containing lectin binding site, CRT C105A, C137A and W319A point mutation resulted in the changes in solvent accessible surface area, key residues' side chain atom positions and dynamical correlated motions between residues. All these changes could directly affect CRT binding behavior. Results of this study provide molecular and structural insights into understanding the role of key residues of CRT in its binding behavior.